A Versatile Methodology for the Controlled Synthesis of Photoluminescent High‐Boron‐Content Dendrimers. Issue 20 (11th March 2013) - González‐Campo, Arántzazu; Ferrer‐Ugalde, Albert; Viñas, Clara; Teixidor, Francesc; Sillanpää, Reijo; Rodríguez‐Romero, Jesús; Santillan, Rosa; Farfán, Norberto; Núñez, Rosario
Abstract Fluorescent star‐shaped molecules and dendrimers with a 1, 3, 5‐triphenylbenzene moiety as the core and 3 or 9 carborane derivatives at the periphery, have been prepared in very good yields by following different approaches. One procedure relies on the nucleophilic substitution of Br groups in 1, 3, 5‐tris(4‐(3‐bromopropoxy)phenyl)benzene with the monolithium salts of methyl and phenyl‐o‐carborane. The second method is the hydrosilylation reactions on the peripheral allyl ether functions of 1, 3, 5‐tris(4‐allyloxy‐phenyl)benzene and 1, 3, 5‐tris(4‐(3, 4, 5‐trisallyloxybenzyloxy)phenyl)benzene with suitable carboranyl‐silanes to produce different generations of dendrimers decorated with carboranyl fragments. This approach is very versatile and allows one to introduce long spacers between the fluorescent cores and the boron clusters, as well as to obtain a high loading of boron clusters. The removal of one boron atom from each cluster leads to high‐boron‐content water‐soluble macromolecules. Thermogravimetric analyses show a higher thermal stability for the three‐functionalized compounds than for those containing 9 clusters. All compounds exhibit photoluminescent properties at room temperature under ultraviolet irradiation with high quantum yields; these depend on the nature of the cluster and the substituent on the Ccluster. Cyclic voltammetry indicates that there is no electronic communication between the core and the peripheral carboranyl fragments. Due to the high boron content of these molecules, we currently focus our research on their biocompatibility, biodistribution in cells cultures, and potential applications for boron neutron capture therapy (BNCT).